2009
DOI: 10.1177/1076029609336856
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Patients Hospitalized With Thyroid Dysfunction

Abstract: The objective of this investigation is to explore a possible role of thyroid dysfunction in venous thromboembolism (VTE). The number of patients discharged from short-stay nonfederal hospitals in the United States, from 1979 to 2005, with a diagnostic code for hypothyroidism or hyperthyroidism, pulmonary embolism (PE), and deep venous thrombosis (DVT) was obtained from the National Hospital Discharge Survey (NHDS). Among 19,519,000 hospitalized patients discharged with a diagnosis of hypothyroidism from 1979 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…In the present study, the apparently U-shaped association between TSH levels and risk of VTE supports previous findings that link both hyperthyroidism and subclinical and overt hypothyroidism to a hypercoagulable state (3,4,5,6,7,8,9,10). Previous case-control and case-cohort studies (21,22) have shown that there is a particular association between elevated levels of FT 4 and a risk of VTE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the apparently U-shaped association between TSH levels and risk of VTE supports previous findings that link both hyperthyroidism and subclinical and overt hypothyroidism to a hypercoagulable state (3,4,5,6,7,8,9,10). Previous case-control and case-cohort studies (21,22) have shown that there is a particular association between elevated levels of FT 4 and a risk of VTE.…”
Section: Discussionsupporting
confidence: 91%
“…A hypercoagulable state has been linked to both hyperthyroidism (3,4,5,6) and subclinical, as well as overt, moderate hypothyroidism (7,8,9,10). A relationship has also been reported between thyroid dysfunction and arterial cardiovascular diseases (CVDs) (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…25 Preterm birth is associated with diabetes and hypothyroidism, 26,27 which have also been associated with increased risk of VTE. 28,29 Cigarette smoking during pregnancy is a risk factor for preterm birth 30 and may be associated with an increased risk of VTE in the offspring. 13 A better understanding of patterns of human plasticity in response to early nutrition and other environmental factors is needed to further elucidate the link between preterm birth and VTE.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation disorders associated with thyroid disease are usually mild and not associated with sudden death. There are some studies showing an increased risk for unprovoked deep venous thrombosis in patients with subclinical hypothyroidism (3)(4)(5), but there is none, to our knowledge, showing a correlation between hypothyroidism, deep venous thrombosis and sudden death. Overt hypothyroidism is known to be associated with an increased risk of bleeding (6).…”
Section: Introductionmentioning
confidence: 88%